MANAGEMENT PATTERNS IN THE PROTOCOL AND SECTION LEADER COMMUNICATION IN BUILDING CREDIBILITY ON CHANGES IN ORGANIZATIONAL FUNCTIONS - Novitha, Ayu; Yamin, Ahmad; Hasrani, Diah Anggraini (Jurnal Manajemen Pelayanan Hotel, 2022)
This article discusses the Protocol Management Pattern and Leader Communication in forming credibility for changes in organizational functions. The Protocol Section and Leader Communication Section at the Regional Secretariat ideally has a strategic position that provides flexibility in carrying out its modern and dynamic functions. This study uses a qualitative method with a descriptive design. The results of the study, that the management of Protocol and Leadership Communication at the Regional Secretariat of Sumbawa Regency is still in the area of delivering information to the public, and has not played a role in strategic decision-making within the organization. Increasing understanding of Public Relations in government is very important, and Protocol and Leadership Communication activities carried out are in the field of public relations science and practice. Keywords: Protocol, Leader Communications, and Information